2005
DOI: 10.1021/jp050075v
|View full text |Cite
|
Sign up to set email alerts
|

Dancing Waves in Reaction−Diffusion Systems

Abstract: The mechanism of pattern formation in reaction-diffusion systems is treated as an interesting subject, generally for understanding self-organization observed in living systems and natural phenomena. Several spatial patterns appear in the reaction-diffusion systems where an activator and an inhibitor coexist as an intermediate, as represented by a traveling wave, a stationary wave called a Turing structure, etc. Here, we show new kinds of waves in reaction-diffusion systems, which exhibit reciprocating motion w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…22 Furthermore, the behavior agreed with simulation results obtained by the GrayÀScott model considering the thickness of the medium. 35 When the medium is thick, the flux in the direction of the thickness is added into the system. The flux affects pattern formation.…”
Section: Resultsmentioning
confidence: 99%
“…22 Furthermore, the behavior agreed with simulation results obtained by the GrayÀScott model considering the thickness of the medium. 35 When the medium is thick, the flux in the direction of the thickness is added into the system. The flux affects pattern formation.…”
Section: Resultsmentioning
confidence: 99%
“…Recently simplified Gray-Scott model extended by the diffusion had been considered [15]. Authors have applied it for description of the 3D patterns observed in experiments.…”
Section: Introductionmentioning
confidence: 99%